ASSESSMENT OF POSTOPERATIVE OUTCOMES IN ELDERLY WOMEN WITH BREAST CANCER (International Conference on Medical Science, Medicine and Public Health, 2025)
Breast cancer (BC) is among the most prevalent malignancies affecting women worldwide and has recently become the leading cause of cancer-related morbidity among females. Globally, approximately 1.3 million new cases are diagnosed annually, with over 500,000 deaths. In Uzbekistan, as in many developed countries, breast cancer incidence is on the rise, with over half of the new cases detected in women over the age of 65. This trend reflects the global demographic shift toward aging populations and increased life expectancy.